MEDIA AUDIOVISUAL PADA PELAJARAN SENI BUDAYA - Hary Murcahyanto; Mohzana Mohzana; Lukluil Himni (LPPM Universitas Gunung Rinjani, 2022)
This study discusses the effect of audiovisual media on learning outcomes of basic movements of Sasak traditional dance in junior high school students. This study aims to describe student learning outcomes before being given treatment (pretest) and after being given treatment (posttest) and to analyze the effect of audiovisual media on learning outcomes of basic movements of traditional Sasak dance in junior high school students. This research method is an experiment with a quantitative approach using the One Group Pretest-Posttest design. The sampling technique used a total sample with a total sample of 49 students from 2 classes. The data collection technique used a test in the form of a description. The data analysis technique used paired sample t-test for paired samples. The results of this study obtained the pretest score of students with an average value of 59.98 and post-test scores with an average of 78.73. After obtaining the student test data, the researcher then analyzed the data using a paired sample t-test for paired samples and obtained the results tcount = -17.488 and sig.(2-tailed) = 0.000 with a significance level of 5% or 0.05. Thus the value of sig.(2-tailed) < 0.05 is 0.000<0.05, which means it is rejected and accepted. Based on the results of the data analysis, it can be concluded that there is an influence of audiovisual media on the learning outcomes of the basic movements of the Sasak traditional dance in junior high school students. Keywords: audiovisual media, cultural arts, traditional dance Abstrak Penelitian ini membahas tentang pengaruh media audiovisual terhadap hasil belajar gerak dasar tari tradisional Sasak pada siswa SMP. Penelitian ini bertujuan untuk mendeskripsikan hasil belajar siswa sebelum diberikan perlakuan (pretest) dan setelah diberikan perlakuan (posttest) serta menganalisis pengaruh media audiovisual terhadap hasil belajar gerak dasar tari tradisional sasak pada siswa SMP. Metode penelitian ini adalah eksperimen dengan pendekatan kuantitatif menggunakan design One Group Pretest-Posttest. Teknik pengambilan sampel menggunakan sampel total dengan jumlah sampel sebanyak 49 siswa dari 2 kelas. Teknik pengumpulan data menggunakan tes berupa uraian. Teknik analisis data menggunakan uji paired sampel t test untuk sampel berpasangan. Hasil penelitian ini, diperoleh nilai pretest siswa dengan nilai rata-rata 59.98 dan nilai posttest dengan rata-rata 78.73. Setelah memperoleh data hasil tes siswa, selanjutnya peneliti melakukan analisis data menggunakan paired sampel t test untuk sampel berpasangan dan memperoleh hasil thitung= -17.488 dan sig.(2-tailed) = 0.000 dengan taraf signifikansi 5% atau 0.05. Dengan demikian nilai sig.(2-tailed) < 0.05 yaitu 0.000<0.05 yang artinya ditolak dan diterima.Berdasarkan hasil analisis data tersebut dapat disimpulkan bahwa adanya pengaruh media audiovisual terhadap hasil belajar gerak dasar tari tradisional Sasak pada siswa SMP.